Cover Image. (14th June 2019) - Pozzi, Federica; Basso, Elena; Rizzo, Adriana; Cesaratto, Anna; Tague, Thomas J.
Abstract : The cover image is based on the Research Article Evaluation and optimization of the potential of a handheld Raman spectrometer: in situ, noninvasive materials characterization in artworks by Federica Pozzi et al., https://doi.org/10.1002/jrs.5585 .